Controller design for a wind turbine system - Wang, Ya Xuan. (2010)
In the long run, an ecologically sustainable energy supply can only be guaranteed by the integration of renewable resources. Besides water power, which is already well established, wind energy is by far the most technically advanced of all renewable power sources, and its economic breakthrough the closest. With a few exceptions, wind power will be used mostly for generating electricity.